Conclave : the politics, personalities, and process of the next papal election - Allen, John L., Jr., 1965- (New York : Image/Doubleday, 2004)
Insider's guide to the politics and personalities that will have a tremendous impact on one of the world's most secretive and important events -- the election of a pope to succeed John Paul II. John L. Allen, Jr., takes readers behind the scenes to reveal the issues, parties, and people most likely to determine the outcome. Setting the election within a broader context, he explains why it matters who becomes pope, discusses their role in the modern world, and examines the issues that will form the agenda of the next papacy.
Includes index.
Keywords: Popes -- Election